(untitled) (Neo Scientific Peer Reviewed Journal, 2026)
This article analyzes the pedagogical and psychological aspects of studying the characteristics of sanogenetic concepts in students. Using empirical methods, indicators of students’ sanogenic thinking, volitional self-control, mental stability, and stress resistance were examined.